Identification and characterization of pteroplinthite mangrove forests - Othman, Rashidi; Wan Daud, Wan Masyitah (Kulliyah of Architecture and Environmental Design, International Islamic University Malaysia, 2018)
Mangroves are highly beneficial as they have many environmental and social functions. This paper is aimed at identifying the unique characteristics of Pteroplinthite Mangrove Forest which is one of the mangrove types in Peninsular which has never been documented so far. This kind of mangrove can support numerous residents and non-residents species. It is important to find out the abiotic and biotic factors affecting how they perceive with their surroundings. The study is also expected to explore the most intrinsic value of Pteroplinthite Mangrove Forests that can be integrated as a landscape design element. These intrinsic values of this mangrove forest are being manipulated to be integrated into the urban landscape design setting.